Långsiktiga effekter av askåterföring och kvävegödsling på skogsmarkvegetationens sammansättning - Ingelsson, Fredrik (2016)
Application of wood ash in forests is a method used to return (recycle) nutrients to the forest that is lost after forest harvesting. There are concerns that such application may influence pants and induce changes in species composition of the ground vegetation. Several studies have examined short-term effects of ash application on ground vegetation, but there few long-term studies have been conducted. The published studies examining the effects on ground vegetation show no consistent pattern in the response. Application of ash has been shown increased forest biomass production, but also influence some plants negatively, resulting in reduced cover of such species. My study is a continuation of a study completed in 2001. In that study, they had six treatments including a control. The various treatments consisted of 3, 6 and 9 tons of ash ha-1, 3 tons of ash + 150 kg N ha-1, 150 kg N ha-1 and 3 tons of pelletized ash ha-1. Inventory data from the study have been compared with inventory data in this study. Using statistical analyzes, my results address the long-term effects (17 yrs) of wood ash application on composition of forest ground vegetation. This shows whether species have increased or decreased after the application of ashes 17 years ago. My results show small differences in cover of plants between controls and plots exposed to wood ash application. Several species showed decreased cover as an initial response to wood ash application, but 17 years after application cover of almost all species had recovered from initial effects of the wood ash application. Some species, Vaccinium myrtillus and Hylocomium splendens even showed a tendency to have higher current cover in the ash treatments than in the controls. The only species that showed significant lower cover in the ash treatments, and showed no sign of recovery was Cladonia rangiferina. I suggest that this most likely is generated by changing competitive conditions. Based on how the ground vegetation responded I find no reason to stop or reduce return of wood ashes to the forestland. However, the long-lasting effects on the ground-living lichen Cladonia rangiferina imply that return of wood ash to areas utilized for reindeer husbandry (that is dependent on lichens as winter forage) should be avoided.